2009
DOI: 10.1124/dmd.109.028043
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Multiple Cytochrome P450 Isoforms by Xanthone Derivatives from Mangosteen Extract

Abstract: ABSTRACT:Mangosteen is a xanthone-containing fruit found in Southeast Asia for which health claims include maintaining healthy immune and gastrointestinal systems to slowing the progression of tumor growth and neurodegenerative diseases. Previous studies have identified multiple xanthones in the pericarp of the mangosteen fruit. The aim of the current study was to assess the drug inhibition potential of mangosteen in vitro as well as the cytochrome P450 (P450) enzymes responsible for the metabolism of its indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…A previous study in human liver microsomes showing inhibition of P450 by MSBE or mangiferin evidenced direct effects on catalytic activities . Similarly, a comparative study with six xanthone derivatives revealed that these structures produce a non selective in vitro inhibition of multiple P450 enzymes, most of which by a competitive inhibition model (Foti et al, 2009). On the other hand, quantification of the P450 mRNA levels in hepatocytes exposed to MSBE and mangiferin revealed enzyme-specific effects: increases for CYP1A1 and 1A2, reductions for CYP3A4 and 3A5, and no changes for the other analyzed isoforms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in human liver microsomes showing inhibition of P450 by MSBE or mangiferin evidenced direct effects on catalytic activities . Similarly, a comparative study with six xanthone derivatives revealed that these structures produce a non selective in vitro inhibition of multiple P450 enzymes, most of which by a competitive inhibition model (Foti et al, 2009). On the other hand, quantification of the P450 mRNA levels in hepatocytes exposed to MSBE and mangiferin revealed enzyme-specific effects: increases for CYP1A1 and 1A2, reductions for CYP3A4 and 3A5, and no changes for the other analyzed isoforms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various processes of carcinogenesis, blocking of tumor initiation through the induction of phase I and II enzymes such as CYP and quinone reductase (QR) is considered as an important cytoprotective mechanism. Xanthones have been reported to induce QR and inhibit P450 activity [46, 47], suggesting that these substances may have potential uses for preventing cancer initiation. Currently, however, there has been limited study regarding the inhibitive effects of xanthones on phase I and II enzymes, and warrant further investigation.…”
Section: Chemopreventive and Chemotherapeutic Potential Of Mangosteenmentioning
confidence: 99%
“…Mangosteen has been found to be both substrate and inhibitor for multiple hepatic cytochomre P450 isoforms 15. Curcumin accelerates liver injury and liver cellular oedema in mice with injured liver 16.…”
Section: Discussionmentioning
confidence: 99%